Smoked cigarette butt leachate impacts survival and behaviour of freshwater invertebrates. (November 2020) - Green, Dannielle Senga; Kregting, Louise; Boots, Bas
Abstract: Smoked cigarette filters a. k.a. "butts", composed of plastic (e.g. cellulose acetate) are one of the world's most common litter items. In response to concerns about plastic pollution, biodegradable cellulose filters are being promoted as an environmentally safe alternative, however, once smoked, both contain toxins which can leach once discarded. The impacts of biodegradable butts as littered items on the receiving environment, in comparison with conventional butts has not yet been assessed. A freshwater mesocosm experiment was used to test the effects of leachate from smoked cellulose acetate versus smoked cellulose filters at a range of concentrations (0, 0.2, 1 and 5 butts L −1 ) on the mortality and behaviour of four freshwater invertebrates ( Dreissena polymorpha, Polycelis nigra, Planorbis planorbis and Bithynia tentaculata ). Leachate derived from 5 butts L −1 of either type of filter caused 60–100% mortality to all species within 5 days. Leachate derived from 1 butt L −1 of either type resulted in adults being less active than those exposed to no or 0.2 butts L −1 leachate. Cigarette butts, therefore, regardless of their perceived degradability can cause mortality and decreased activity of key freshwater invertebrates and should always be disposed of responsibly. Graphical abstract: Image 1 Highlights: Effects of leachate from cellulose acetate vs cellulose cigarette butts were tested. Cigarette butt leachate (5 butts L −1 ) was acutely toxic to freshwater invertebrates. After 120 h leachate from 1 butt L −1 killed 60% of juvenile B. tentaculata. There was a decrease in activity in invertebrates exposed to 1 butt L −1 leachate. Leachate from biodegradable butts caused the same impact as conventional butts. Abstract : As litter in enclosed aquatic habitats, conventional and biodegradable cigarette butts have the same effects causing mortality and behavioural changes to invertebrates.